Efficacy of computerized cognitive training using mobile devices to promote cognitive functioning in community-dwelling older adults with or without risk of mild cognitive impairment: A multi-centre longitudinal study - Kenneth N K Fong; Alex W K So; Kevin C H Cheung; Jack Y L Cheung; Anson M H Lee; Ryan C Y Wong; Joyce S Y Lau; Pablo Cruz Gonzalez; Wilson W S Wong; Danny K F Li; Diana S H Kam (Digital Health)
Objective To investigate the efficacy of a 5-month computerized cognitive training programme (CCT) “Exercise your Brain” using mobile devices in improving cognitive functioning in community-dwelling older adults with and without risk of mild cognitive impairment (MCI). Methods One hundred thirty-four older adults were recruited from 5-day activity centres for the older adults in Hong Kong using convenience sampling to participate in a 5-month CCT training. Participants were stratified into older adults with and without risk of MCI. Results There was significant improvement (p < 0.001) in MoCA 5-min for the whole sample after 5-month CCT (d = 0.72) and the effects were maintained at 3-month follow-up. The group at risk of MCI improved their cognitive functioning immediately after intervention more than the non-MCI group (p < 0.001, d = 1.37 vs d = 0.55). In the task-based performance, there was significant interaction effect between memory and calculation with and without risk of MCI when years of formal education was a covariate, and that the non-MCI group had the highest improvement in Judgement (6.23%) and memory (5.43%), compared with that (1.47% and 2.33%) in the group at risk of MCI. The risk-of-MCI group had the highest improvement in attention (2.67%) and eye-hand coordination (4.87%), compared with that of the healthy older adults. Conclusion Cognitive functioning in both older adults with or without risk of MCI was enhanced immediately after CCT using a mobile device and endured over a three-month follow-up. The training effect on the group at risk of MCI was significantly greater than that for the non-MCI group. With recent advances in mobile technology, remote cognitive training in terms of using mobile devices for older adults as primary and secondary preventions is applicable and practicable.